2012
DOI: 10.1186/1477-5956-10-16
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of soybean defense response induced by cotton worm (prodenia litura, fabricius) feeding

Abstract: BackgroundCotton worm is one of the main insects of soybean in southern China. Plants may acquire defense mechanisms that confer protection from predation by herbivores. Induced responses can lead to increased resistance against herbivores in many species. This study focuses on searching changed proteins in soybean defense response induced by cotton worm feeding.ResultsTen protein spots that are changed in abundance in response to cotton worm feeding were identified by Two-dimensional gel electrophoresis (2-DE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 71 publications
1
17
0
Order By: Relevance
“…The levels of S-adenosylmethionine synthetase have also been shown to increase in response to cold stress in rice (71), mechanical wounding in lima bean (72), salinity stress in barley (73), and as part of defense responses to cotton worm feeding in soybean (74). Furthermore, it was reported that the levels of S-adenosylmethionine synthetase are decreased in flooded soybean, indicating that this enzyme plays a central role in the response to flooding in soybean (13,14).…”
Section: Accepted Manuscriptmentioning
confidence: 95%
“…The levels of S-adenosylmethionine synthetase have also been shown to increase in response to cold stress in rice (71), mechanical wounding in lima bean (72), salinity stress in barley (73), and as part of defense responses to cotton worm feeding in soybean (74). Furthermore, it was reported that the levels of S-adenosylmethionine synthetase are decreased in flooded soybean, indicating that this enzyme plays a central role in the response to flooding in soybean (13,14).…”
Section: Accepted Manuscriptmentioning
confidence: 95%
“…In our previous research, 11 proteins were identified from the proteome of NN soybean leaves damaged by common cutworm feeding (Fan et al . ), of these proteins, serine/threonine kinase‐related protein and VSP α were also shown to have transcriptome changes. The correlation between transcripts and proteins was observed to be good on specific targets (Zulak et al .…”
Section: Discussionmentioning
confidence: 98%
“…We previously identified an induced resistance response caused by the feeding of common cutworms in a susceptible soybean line, and we detected 11 differently expressed proteins that may be involved in this induced defence response using proteomic approaches (Fan et al . ). However, the biochemical mechanisms and signalling pathways of the induced response in soybeans that leads to the decreased herbivore preference and/or performance are still poorly understood.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Overexpression of suadea salsa SAMs gene promoted salt tolerance in transgenic tobacco (Qi et al, 2010). An increase in production of SAMs was observed in cold stressed rice (Cui et al, 2005), mechanically wounded Phaseolus lunatus (Arimura et al, 2002), salt-stressed barley (Witzel et al, 2009), and in response to cotton worm feeding in soybean (Fan et al, 2012). Hence, the remarkable expression of SAMs by NSY50 suggested that plant might promote SAM-dependant metabolism through synthesize more SAM to further enhance the synthesis of new proteins and stress tolerance.…”
Section: Discussionmentioning
confidence: 99%